2013
DOI: 10.1016/j.neuron.2013.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Regulates Its Own Receptor on Postcrossing Commissural Axons in a Glypican1-Dependent Manner

Abstract: Upon reaching their intermediate target, the floorplate, commissural axons acquire responsiveness to repulsive guidance cues, allowing the axons to exit the midline and adopt a contralateral, longitudinal trajectory. The molecular mechanisms that regulate this switch from attraction to repulsion remain poorly defined. Here, we show that the heparan sulfate proteoglycan Glypican1 (GPC1) is required as a coreceptor for the Shh-dependent induction of Hedgehog-interacting protein (Hhip) in commissural neurons. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 57 publications
5
97
0
Order By: Relevance
“…The efficiency of gene silencing by miRNAs (supplementary material Figs S1 and S2) was assessed by in situ hybridization (Wilson and Stoeckli, 2013) and by in vitro screening (Wilson and Stoeckli, 2011). For quantitative analysis of knockdown, the ratio between the signal intensities (grayscale values) of Sema6B or PlxnA2 and the corresponding fluorescent protein from the co-transfected miRNA constructs was calculated using ImageJ (NIH) and subsequently normalized to the miLuc control condition.…”
Section: In Ovo and In Vitro Rnaimentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of gene silencing by miRNAs (supplementary material Figs S1 and S2) was assessed by in situ hybridization (Wilson and Stoeckli, 2013) and by in vitro screening (Wilson and Stoeckli, 2011). For quantitative analysis of knockdown, the ratio between the signal intensities (grayscale values) of Sema6B or PlxnA2 and the corresponding fluorescent protein from the co-transfected miRNA constructs was calculated using ImageJ (NIH) and subsequently normalized to the miLuc control condition.…”
Section: In Ovo and In Vitro Rnaimentioning
confidence: 99%
“…Axonal repulsion is induced by the upregulation of Robo1 on the growth cone surface, which allows for the detection of Slit, a negative floorplate-derived signal (Philipp et al, 2012). Axonal navigation at the floorplate exit site is subsequently directed by F-spondin (Burstyn-Cohen et al, 1999), SynCAMs/Nectin-like molecules (Niederkofler et al, 2010), MDGA2 (Joset et al, 2011), and the morphogens Wnts (Lyuksyutova et al, 2003;Domanitskaya et al, 2010) and sonic hedgehog (Shh) (Bourikas et al, 2005;Wilson and Stoeckli, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The direct repulsive effect on postcrossing axons is mediated by Hhip (Bourikas et al, 2005). Recently, we demonstrated that Shh itself regulates the expression of Hhip in a glypican 1-dependent manner (Wilson and Stoeckli, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Robo1 and RabGDI, loss of calsyntenin 1 had an additional effect on post-crossing commissural axons. Like Shh (Bourikas et al, 2005;Wilson and Stoeckli, 2013), Wnts (Domanitskaya et al, 2010;Avilés and Stoeckli, 2016), SynCAMs (Niederkofler et al, 2010) and semaphorin 6B (Andermatt et al, 2014), calsyntenin 1 was required for the rostral turning of postcrossing commissural axons. Our detailed in vivo analyses indicate a regulatory role of calsyntenin 1-mediated trafficking in midline crossing by controlling Robo1 expression and in longitudinal axon guidance by controlling frizzled 3 expression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, axons must adjust their responsiveness to extracellular cues as they migrate through the embryo, and transcriptional regulation provides a mechanism to achieve this control (Keleman et al, 2002;Wilson and Stoeckli, 2013). In Drosophila embryos, the Frazzled/DCC receptor is required for induction of the commissureless gene, which encodes a key regulator of midline crossing, suggesting that axon guidance receptors themselves can play a role in regulating changes in gene expression during neural circuit formation (Yang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%